Who is likely to develop persistent low back pain? A longitudinal analysis of prognostic occupational factors - Melloh, Markus; Elfering, A.; Stanton, T.; Käser, A.; Salathé, C.; Barz, T.; Röder, C.; Theis, J. (2013)
Objective: Occupational low back pain (LBP) is considered to be the most expensive form of work disability, with the socioeconomic costs of persistent LBP exceeding the costs of acute and subacute LBP by far. This makes the early identification of patients at risk of developing persistent LBP essential, especially in working populations. The aim of the study was to evaluate both risk factors (for the development of persistent LBP) and protective factors (preventing the development of persistent LBP) in the same cohort. PARTICIPANTS: An inception cohort of 315 patients with acute to subacute or with recurrent LBP was recruited from 14 health practitioners (twelve general practitioners and two physiotherapists) across New Zealand. Methods: Patients with persistent LBP at six-month follow-up were compared to patients with non-persistent LBP looking at occupational, psychological, biomedical and demographic/lifestyle predictors at baseline using multiple logistic regression analyses. All significant variables from the different domains were combined into a one predictor model. Results: A final two-predictor model with an overall predictive value of 78% included social support at work (OR 0.67; 95%CI 0.45 to 0.99) and somatization (OR 1.08; 95%CI 1.01 to 1.15). Conclusions: Social support at work should be considered as a resource preventing the development of persistent LBP whereas somatization should be considered as a risk factor for the development of persistent LBP. Further studies are needed to determine if addressing these factors in workplace interventions for patients suffering from acute, subacute or recurrent LBP prevents subsequent development of persistent LBP. © 2013 - IOS Press and the authors. All rights reserved.